Different frequential acceleration spectrums in front crawl - Madera, J.; Gonzalez, L. M.; Garcia Masso, X.; Benavent, J.; Colado, J. C.; Tella, V. (Biomechanics and Medicine in Swimming XI, 2010)
This study analyzes the three different spectrums that define the acceleration produced by front crawl swimmers during a high speed test. These swimmers (n=79) performed 25 meters at maximum speed. The acceleration was obtained from the position-time data recorded using a position transducer. The amplitude in the time domain was calculated with the root mean square (RMS); while the peak power (PP), the peak power frequency (PPF) and the spectrum area (SA) were calculated in the frequency domain with Fourier analysis. An ANOVA to establish differences between groups (spectrums) was applied. Results show three different spectrum types (type 1: 27,85%, type 2: 30,38% and type 3: 41,77%). Our work shows that type 1 frequential spectrum is related to more coherence and might discriminate to the swimmers with better RMS.